Factors A New Paradigm of Sustainability: Integrating Circular Economy, Inclusive Capitalism, and Christian Ethics - Šetek, Jaroslav; Alina, Jiří; Bartůňková, Tereza (European Journal of Sustainable Development, 2025)
Since the early 2020s, the global community has been grappling with mounting environmental and social challenges that question the viability of traditional models of economic development and societal advancement. This paper explores four conceptual approaches: Inclusive Capitalism, Integral Ecology, Christian Social Ethics, and the Circular Economy, with the intention of fostering a new model of equitable and lasting development. It demonstrates how connecting these frameworks can enable a systemic transformation beyond sector-specific solutions, highlighting ethical responsibility, justice between generations, and active participation. The article highlights the importance of the Christian ethos and spirituality in restoring the human relationship with both nature and society, thereby suggesting one possible path toward a more just and sustainable economic order. Within this context, the Circular Economy emerges as a key instrument for restoring economic and ecological relations through the promotion of efficient resource use, waste minimization, and the strengthening of local resilience. The innovative trends of circular technologies thus become a vital pillar in the transition toward an ethically grounded and environmentally sustainable future. Keywords: circular economy, sustainable development, inclusive capitalism, integral ecology, responsible investments